PROFILE OF CUTANEOUS ADVERSE DRUG REACTIONS IN PATIENTS ATTENDING THE DERMATOLOGY OUTPATIENT DEPARTMENT OF A TERTIARY CARE HOSPITAL, GANGTOK - Bhutia, Karma Tenzing; Sharma, Chandrakala; Sharma, Rukma lal (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The present study was undertaken to evaluate the frequency of occurrence of cutaneous adverse drug reactions (ADRs) in patients attending dermatology outpatient department (OPD) and to assess causality and severity of the reported cutaneous ADRs, using different scales. Methods: The study involved descriptive through retrospective review of patient medical records for patients who attended dermatology OPD for a period of 9 months. Patients’ records specifying with cutaneous ADRs were taken for the study. Results: The record of 30 patients reported with cutaneous ADRs with certain exclusions was studied. Higher incidence was found among females with 20–40 years of age. The most common presenting symptom was found to be erythematous rash (33%) and the drug groups involved in reactions were NSAIDS, beta-lactams, antitubercular drugs, and antifungals (16.7% each). The most common drug associated with cutaneous ADRs (CADRs) was itraconazole and aceclofenac (16.7% each). On the Naranjo scale, 86% reactions were labeled as “possible” while others as “doubtful”. All the reactions were labeled as mild on Hartwig’s Severity Assessment Scale. Conclusions: Lack of post-treatment follow-up could be a reason for the difference in the causality result as compared to other studies. The data recorded in this study can be utilized as reference for future studies with large population.